2001
DOI: 10.1089/089771501750055730
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychology of Blunt Head Injury in the Early Postacute Stage: Effects of Focal Lesions and Diffuse Axonal Injury

Abstract: This investigation evaluated the neuropsychological symptoms in the early posttraumatic period following blunt head injury and their correlation to routine imaging data in a consecutive series of TBI patients (Magdeburg Neurotrauma Databank). Of 135 consecutive patients, 68 could be assessed neuropsychologically 8-21 days after trauma. In 61 patients, routine clinical CT data were sufficient for neuroradiological analysis focusing on the presence or absence of CT signs of diffuse axonal injury (DAI) or focal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 16 publications
3
52
0
4
Order By: Relevance
“…In addition, executive processes might be involved in reduced productivity in performing the Block Design, Picture Arrangement and Picture Completion tests (Lezak, 1995). Indeed, based on the literature, we expected more impairment in both the VaD and sVaD group for the following of these tests: Block Design (Johnson, Head, Kim, Starr & Cotman, 1999;Skranes et al, 1997;Wallesch, Curio, Galazsky, Jost & Synowitz, 2001), Digit Symbol Substitution (Boone, Pontón, Gorsuch, González & Miller, 1998;Mahurin, Velligan & Miller, 1998;Peavy et al, 2001), Picture Arrangement (Deckel, 1999;Hasselbalch et al, 1992;Peavy et al, 2001), and Picture Completion (Mahieux et al, 1998;Skranes et al, 1997). Also, the Object Assembly test does reveal frontal processing (Peavy et al, 2001;Randolph et al, 1993) and might involve an executive component.…”
Section: Methodsmentioning
confidence: 87%
“…In addition, executive processes might be involved in reduced productivity in performing the Block Design, Picture Arrangement and Picture Completion tests (Lezak, 1995). Indeed, based on the literature, we expected more impairment in both the VaD and sVaD group for the following of these tests: Block Design (Johnson, Head, Kim, Starr & Cotman, 1999;Skranes et al, 1997;Wallesch, Curio, Galazsky, Jost & Synowitz, 2001), Digit Symbol Substitution (Boone, Pontón, Gorsuch, González & Miller, 1998;Mahurin, Velligan & Miller, 1998;Peavy et al, 2001), Picture Arrangement (Deckel, 1999;Hasselbalch et al, 1992;Peavy et al, 2001), and Picture Completion (Mahieux et al, 1998;Skranes et al, 1997). Also, the Object Assembly test does reveal frontal processing (Peavy et al, 2001;Randolph et al, 1993) and might involve an executive component.…”
Section: Methodsmentioning
confidence: 87%
“…The three assessment techniques do not always coincide. Wallesch et al (2001) found only 3 of 13 measures had significant correlations ranging from -.54 to .45 between initial GCS ratings and neuropsychological measures of memory, reaction time, executive functions administered 8-21 days post injury. The sample included subjects with documented diffuse axonal injury (DAI) on CT and MRI scans.…”
Section: The Neuropsychological Evaluation Of Traumatic Brain Injurymentioning
confidence: 84%
“…The inconsistency of the results between the two constructive subtests might be due to the requirement of attention and executive function for performing the WAIS-R block design subtest [17] . Patients with frontal lobe contusions were impaired in the WAIS-R block design subtest [18] . On the other hand, patients with frontotemporal dementia with hypoperfusion in the frontal lobe could copy simple fi gures such as those used in the ADAS construction subtest [19] .…”
Section: Discussionmentioning
confidence: 98%